2007
DOI: 10.1111/j.1748-1716.2007.01737.x
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine‐sensitive noradrenergic vasoconstriction is enhanced in spontaneously hypertensive rats: the influence of chronic captopril treatment

Abstract: The contribution of nifedipine-sensitive component to noradrenergic vasoconstriction is enhanced during excessive NE stimulation (increased sympathetic tone of SHR in vivo or supramaximal NE stimulation in vitro). It seems that captopril-induced reduction of central sympathetic tone is able to normalize augmented nifedipine-sensitive vasoconstriction in SHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Nelson et al 40 described the activation of L-VDCCs after norepinephrine stimulation, which results in an enhanced Ca 2+ influx. Our earlier study 4 demonstrated that a Ca 2+ influx through L-VDCCs during the tonic phase of norepinephrineinduced vascular contraction represents a decisive part of enhanced sympathetic vasoconstriction in SHRs. Moreover, Kuneš et al 5 reported an increased nifedipine-sensitive BP component in all three forms of experimental hypertension examined in the present study.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Nelson et al 40 described the activation of L-VDCCs after norepinephrine stimulation, which results in an enhanced Ca 2+ influx. Our earlier study 4 demonstrated that a Ca 2+ influx through L-VDCCs during the tonic phase of norepinephrineinduced vascular contraction represents a decisive part of enhanced sympathetic vasoconstriction in SHRs. Moreover, Kuneš et al 5 reported an increased nifedipine-sensitive BP component in all three forms of experimental hypertension examined in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…3,4 All these forms of experimental hypertension are characterized by sympathetic hyperactivity leading to an enhanced Ca 2+ influx through L-type voltage-dependent Ca 2+ channels (L-VDCCs), which is reflected by an enhanced BP response to the acute administration of Ca 2+ channel blockers, such as nifedipine. 4,5 Much less attention has been paid to vasodilator systems (except for NO) in various forms of experimental hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of enhanced calcium entry through L-type voltagedependent calcium channels (L-VDCCs) in genetic hypertension is well known [6][7][8][9], but less attention has been paid to the changes of calcium sensitization (mediated by RhoA/Rho kinase pathway) in spontaneously hypertensive rats (SHRs) [10][11][12]. Recently, we have demonstrated that basal calcium sensitization [determined in animals subjected to a blockade of major pressor systems -sympathetic nervous system (SNS) and renin-angiotensin system (RAS)] is decreased in adult SHR compared with Wistar-Kyoto (WKY) controls [13].…”
Section: Introductionmentioning
confidence: 99%